Acute Lymphoblastic Leukemia and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The incidence, timing, etiologies, and recurrence rate of seizures among 127 pediatric patients with acute lymphoblastic leukemia (ALL) were determined at the Schneider Children's Hospital, and the Long Island Jewish Medical Center, New York.